2021 Kansas State University Industrial Hemp Dual-Purpose Variety and Planting Date Trials - Kraig Roozeboom; Jason Griffin; Andrew Euler; Ike Bahr; Brian Owuoche (Kansas Agricultural Experiment Station Research Reports, 2023)
Hemp is a broad term used to describe the many varieties ofCannabis sativaL. that produce less than 0.3% tetrahydrocannabinol (THC). The crop is globally significant, but only recently was allowed to be grown again in the United States. There are many uses for industrial hemp, and the market for industrial hemp is rapidly growing as more states are legalizing its production. The market for industrial hemp exceeded $205 million in 2020 and could surpass $310 million by 2028 (Global Market Insights Inc., 2020). The main components of the industrial hemp market are oil, seeds, and fiber. Varieties have been selected for improved fiber and grain production that can service these markets. However, little research-based information is available regarding adaptability or production of these varieties in Kansas (Griffin et al., 2020; 2021). Hemp could be used to diversify both crop rotations and market opportunities for growers. In 2021, Kansans were allowed to apply for research licenses to grow industrial hemp for the third year. Limited data from the 2019 and 2020 growing season demonstrated vast differences in growth and yield in Kansas. Therefore, ongoing variety trials are necessary to determine which varieties are best adapted to the state. Currently, farmers in Kansas must rely on the limited data from Kansas trials combined with information generated from other states, which have vastly different growing conditions than Kansas. Variety selection is vital in hemp production considering latitude (day length) and length of growing season influence the planting date, number of days to harvest, and ultimately yield. The objectives of this research were to evaluate commercially available varieties of industrial hemp and the effect of planting date on a subset of those varieties at two locations in Kansas (Wichita and Manhattan).
Keywords: hemp; varieties; fiber; grain; dual-purpose